Assessment of prison life of persons with disability in Ghana. Issue 1 (December 2016) - Dogbe, Joslin; Owusu-Dabo, Ellis; Edusei, Anthony; Plange-Rhule, Gyikua; Addofoh, Nicholas; Baffour-Awuah, Sandra; Sarfo-Kantanka, Osei; Hammond, Charles; Owusu, Michael
Abstract Background Persons with Disabilities (PWDs) are a unique group that are often overlooked in many developing countries due to systemic weaknesses, lack of political commitment and inadequate support from government and non-governmental agencies. The population of these individuals is however steadily on the increase and currently corresponds to 15 % of the world population. Although much data exist on lifestyle and conditions of prisoners with disabilities in the western world, scanty information is available in Africa. In Ghana, there is insufficient data on the occurrence and social characteristics of prisoners with disabilities. The purpose of this current study was therefore to identify the occurrence, types and causes of disabilities among prisoners serving sentences in Ghanaian prisons. Methods This study was a descriptive cross-sectional survey conducted in the Male and Female Regional Prisons in Kumasi, Sunyani and the Nsawam Medium Security Prison, from November to December 2011. PWDs were selected by prisons officers and interviewed using structured questionnaires on variables such as socio-demographic characteristics, causes of disabilities and accessibility to recreational facilities. Ethical approval was obtained from the security services and the Committee of Human Research Publications and Ethics (CHRPE) of the School of Medical Sciences, Kwame Nkrumah University of Science and Technology (KNUST). Results We screened 6114 records of prisoners of which 1852 (30.3 %) were from the Kumasi Central Prisons, 3483 (57 %) from the Nsawam Medium Security and 779 (12.8 %) from the Sunyani Central Prisons. A total of 99 PWDs were identified with the commonest disability being physical, followed by visual, hearing, speech, mental and albinism. Most of the disabilities were caused by trauma (68.8 %) followed by infection (16.7 %), and drug related mental disabilities (6.3 %). Fifty (50.5 %) out of the 99 PWDs were not provided with assistive devices although they admitted the need for such. Conclusion The present study has demonstrated the occurrence and conditions of PWDs in Ghanaian prisons. Major stakeholders including government agencies and other organisations could develop policies that would improve the conditions and livelihood of prisoners with disabilities in Ghana.